ORAL CORRECTIVE FEEDBACK FOR STUDENTS OF DIFFERENT PROFICIENCY LEVELS - Bhuana, Gartika Pandu (2014)
This study was aimed to investigate the use of oral corrective feedback for students' of different proficiency levels and the types of corrective feedback contributing to more uptake. It was also aimed to reveal the students' attitude to the use of oral corrective feedback. The study employed a qualitative case study design. The data were gathered from two main sources, which were classroom observation and interview. This study revealed three findings. Firstly, there was a difference in number of types of corrective feedback used for low, mid and high proficiency students. Of the eight types of corrective feedback proposed by Lyster and Ranta (1997), Panova and Lyster (2002), and Ellis (2009), all of them were used to correct the error in low level. Meanwhile, there were only seven types of corrective feedback used in mid level, and five types of corrective feedback used in high level. Secondly, each types of corrective feedback had a different effect on the uptake in each level. In low level, the types of corrective feedback which provided the students with the corrected form of their error (input providing feedback), such as recast and explicit correction, resulted in more number of uptake compared to the types of feedback which prompted the students to do self-correction (output prompting feedback), such as metalinguistic feedback, repetition, and paralinguistic signal. On the other hand, in mid and high levels, output prompting feedback resulted in more number of uptake rather than input providing feedback. Third, most of the students in three proficiency levels had positive attitude to the implementation of corrective feedback. Unfortunately, some of low level students felt embrrassed and afraid of making mistakes after they got the correction from the teacher. Based on the findings above, this study recommends the teacher apply the corrective feedback by suiting them with the students' proficiency levels. It is because what is appropriate for some students might not be appropriate for other students. Moreover, it suggests that the teacher considers the students' feeling in the implementation of corrective feedback. In this case, corrective feedback might be done carefully in very positive way. Thus, it does not directly blame the students who make an error